The International Legal Organization of the Crime of Genocide - Khalid Mohammad Al-Ahmari; Ahmed Salim Ataya (International Journal of Law Research and Studies, 2024)
The research aims to study the crime of genocide and understand the elements of this crime according to a descriptive analytical approach that explains the nature of genocide and the elements and foundations that constitute this crime. The study is divided into two sections: the first section defines the crime of genocide and identifies the characteristics that distinguish it from the crime of ethnic cleansing, while the second section examines the elements of the crime of genocide, reviewing the four elements on which it is based: legal, international, material, and moral. This study reached several conclusions, the most important of which are: the crime of genocide is one of the most dangerous crimes against the international community and represents a blatant violation of the principles of international humanitarian law. The crime of genocide receives significant attention from the international community, particularly in terms of statutes of limitations, general amnesty, and immunity, as the perpetrator of genocide is deprived of all these protections regardless of how long it takes to commit the crime, the perceived magnitude of the crime, or their rank in the state—from the simplest official to the head of state. The study concluded with several recommendations, the most important of which is to expand the concept of genocide in Article 6 to include other groups such as political groups and cultural groups, and to incorporate this into the Rome Statute of the International Criminal Court. It is necessary to address the gaps in the Genocide Convention, such as those related to the specific intent, which is difficult to prove, as well as the targeted groups, clarifying what the intent for the partial destruction of groups is.